REPLY TO LOXTERKAMP. Issue 45 (5th January 2017) - Cahn, Steven M.; Vitrano, Christine
Abstract : Max Loxterkamp correctly attributes to us the view that people are living well if they act morally and find long-term satisfaction, regardless of the pursuits they choose. He disagrees with us, however, and suggests that lives are better if they benefit society, and he offers as examples a charity worker, a courageous soldier, and a philosopher of genius.